2021
DOI: 10.1111/epi.17110
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal slow wave events predict epilepsy following a first seizure

Abstract: Objective: Management of a patient presenting with a first seizure depends on the risk of additional seizures. In clinical practice, the recurrence risk is estimated by the treating physician using the neurological examination, brain imaging, a thorough history for risk factors, and routine scalp electroencephalogram (EEG) to detect abnormal epileptiform activity. The decision to use antiseizure medication can be challenging when objective findings are missing.There is a need for new biomarkers to better diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…When searching for the presence of PSWEs, consistent with previous studies we found that epilepsy patients have significantly more PSWEs compared with healthy controls ( Figure 3 ) [ 11 , 13 ]. Unlike our hypothesis, the temporal characteristics of EEG slowing in PD patients did not show a significant difference in the number of PSWEs compared with control ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When searching for the presence of PSWEs, consistent with previous studies we found that epilepsy patients have significantly more PSWEs compared with healthy controls ( Figure 3 ) [ 11 , 13 ]. Unlike our hypothesis, the temporal characteristics of EEG slowing in PD patients did not show a significant difference in the number of PSWEs compared with control ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, reduced spontaneous eye movement as a manifestation of hypomimia, a common PD symptom, may contribute to this observation. Additionally, similar trends regarding frontal PSWE in epilepsy patients were found in a previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations